The Challenges and Opportunities; CIPP Model for Evaluation for TEFL Following the COVID-19 Pandemic - Mustangin, Muhammad; Riswanto, Beny (STMIK Komputama Majenang, 2020)
This study are focused in : (1) how the context of the Online teaching learning process program on Covid-19 outbreak. (2) how the input of the Online teaching learning process program on Covid-19 to the success program, (3) how far the challenge and the opportunities of the Online teaching learning process program on Covid-19 pandemic. The objects of this study were: the English teacher in government’ schools and private school of junior high school and senior high school, and the students. The data were obtained from interview, classroom observation, and document analysis. Those data were analyzed by using Context, Input, Process, Product (CIPP) Model by Kellaghan and Stufflebeam (2003). The findings revealed some facts. First, in the context evaluation, it can be concluded that the online teaching and learning program are relevant and formulated in order to meet the students’ needs on this pandemic. Second, in term of input evaluation, the teacher did not fulfill the requirements of a qualified teacher yet. Therefore, this pandemic has become a challenge for educators especially for English teachers and students in higher education level. It impacted classrooms to be hardly. Here, the researcher advice the government to conduct a training and workshop in order to improve the quality and the professionalism.